Additions to Andiorrhinus (Turedrilus) (Rhinodrilidae, Clitellata) from Eastern Amazonia - Hernández-García, Luis Manuel; Bartz, Marie Luise; Burgos-Guerrero, Jesús Enrique; Sousa, Sandriel Costa; Rousseau, Guillaume Xavier; James, Samuel Wooster (Zootaxa, 2018)
Two new species of the earthworm family Rhinodrilidae (Clitellata), from Maranhão state, Brazil, were studied by dissection. Andiorrhinus (Turedrilus) miricuri n. sp. is the first record of a big earthworm for this region with three pairs of large spermathecae in segments 7–9 and one pair of tubercula pubertatis bands lateral to b line in XX–XXV. Andiorrhinus (Turedrilus) barrosoi n. sp. lacks spermathecae and has one pair of tubercula pubertatis bands lateral to b line in XX–(1/3) XXIV. The earthworms described are from the most threatened region of Amazonia where 75% of forest cover is already lost. More information is urgently necessary to assess their ecology and vulnerability status.